Petrographic atlas : characterisation of aggregates regarding potential reactivity to alkalis : RILEM TC 219-ACS recommended guidance AAR-1.2, for use with the RILEM AAR-1.1 petrographic examination method /: characterisation of aggregates regarding potential reactivity to alkalis : RILEM TC 219-ACS recommended guidance AAR-1.2, for use with the RILEM AAR-1.1 petrographic examination method. (2016) - Unknown
No abstract available